Preparation of Microcapsules Containing Grape Polyphenols and I-Tocopherol by Spray-Gelling Method (Global Journal of Medical Research, 2014)
It was tried to prepare the microcapsules containing the (W/O) emulsion or the (S/O) dispersion by the Spray-Gelling method. The shell material was gelled sodium alginate. In the case of preparation of the microcapsules containing the (W/O) emulsion, grape polyphenol as the first core was dissolved in the inner water droplets which were dispersed in α-tocopherol oil as the second core. In the case of preparation of the microcapsules containing the (S/O) dispersion, grape polyphenol powder as the first core was dispersed in the α-tocopherol oil as the second core. Two kinds of multiple emulsions such as the (W/O)/W emulsion and the (S/O)/W emulsion, in which the sodium alginate aqueous solution was the continuous water phase, were prepared and sprayed into the calcium chloride aqueous solution as the gelling agent through the nozzle. The microcapsules with the mean diameters from 20 to 70 μm could be prepared. The microencapsulation efficiency was increased by changing the (W/O) emulsion to the (S/O) dispersion.
Keywords: sodium alginate microcapsule; multiple emulsion; grape polyphenol; spray-gelling method; dual core materials; #x3B1; -tocopherol